On The IFRS Discussion Paper Business Combinations: Disclosures, Goodwill and Impairment - Costa Júnior, Jorge Vieira da; Silva, Ricardo Luiz Menezes da; Nakao, Sílvio Hiroshi; Ribeiro, Douglas Tadeu de Oliveira; Machado, Camila Araújo; Domeneghetti, Valdir; Ostanel, Carlos Eduardo; Cosenza, José Paulo; Gomes, Alexandre Cunha (Revista de Contabilidade do Mestrado em Ciências Contábeis da UERJ, 2023)
In 2020, the IFRS Foundation released the document Discussion Paper DP/2020/1: Business Combinations—Disclosures, Goodwill and Impairment (hereafter DP), according to the Post-Implementation Review of IFRS 3. The objective of the paper is to analyze, criticize and make propositions from the previous literature on the IASB's proposals for changes to goodwill accounting. For that, a working group of nine Brazilian academics built on a comment letter in response to the DP. Unlike a traditional article in the accounting area, the investigation of this research was based on the use of previous literature to observe the proposals for changes of the DP. This paper also provides reviews of prior research, assessments, discussions, suggestions for definitions and principles, and suggestions for further research related to disclosures about acquisitions, the effectiveness of the impairment test, the amortization of goodwill, the simplification of the impairment test, the separation of intangibles from goodwill, and the converging practices with the US GAAPs. The results indicated: i) the disclosure about acquisitions should focus on the monitoring of the success or failure of the acquisition; ii) the impairment standard does not present technical problems of effectiveness; iii) the acquired goodwill should be amortized over the time in which the manager expects to recover that investment; iv) an impairment test should be run when an adverse event happens and not annually; v) intangibles should continue to be recognized separately from goodwill; vi) and the change to the amortization model will probably converge with the US GAAPs. Moreover, from the point of view of previous scientific knowledge, it is possible to observe that some problems raised by the literature are considered in the problems pointed out by the standard-setter in the DP; the management of goodwill impairment results is the main one, widely reported in the literature in several aspects, such as timeliness, relevance and manager behavior. Finally, the results provide insights that can contribute to the IASB’s standard-setting process and to the literature on goodwill reporting.